Sustainable Development Working Group Work Plan for 2015-2017. - Sustainable Development Working Group (SDWG) (Sustainable Development Working Group (SDWG), 2015)
Work plan for the year 2015-2017, submitted by the Arctic Council working group Sustainable Development Working Group (SDWG) to the Senior Arctic Officials meeting in Whitehorse, Canada, March 4-5 2015.